MANAGING SPORT EVENTS - Greenwell, T. Christopher; Danzey-Bussell, Leigh Ann; Shonk, David J. (Human Kinetics, 2025)
"This textbook guides students in introductory courses in sport event management and facility management through the process of managing events, from event conception to postevent evaluation. The text addresses key planning areas, including staffing, budgeting, marketing, promotion, sponsorship, and legal and risk management; key operational areas such as services, logistics, and on-site management; and postevent duties and considerations"-